LEARNING FROM PALU: REBUILDING A BETTER CITY IN THE AFTERMATH OF NATURAL DISASTER - Prawita Meidi Handayani; Poetika Puspasari (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2020)
Indonesia is the largest archipelagic country located in the ring of fire, which puts it at a high risk of natural disasters. Earthquakes, tsunami, and liquefaction that occurred in Palu in 2018 that resulted in significant material and immaterial losses were some of the examples.  The earthquake and tsunami resulted in a total casualty of 1.347 people and caused the loss of access to clean water and electricity, as well as a change in the geographical structure and landscape of the city of Palu. Thus, the purpose of this study is to analyze the implementation of post-disaster rehabilitation and reconstruction in the city of Palu using a qualitative research methodology. In addition to that, this study also discusses the relationship between Palu disaster, human security, and national defense. Qualitative research in a descriptive manner that offers a complete description and analysis regarding Palu disaster was held to answer the research question presented in this paper. The results show that the natural disasters that occurred in Palu in 2018 brought about an impact on people's lives and all aspects of human security. This is because, in each phase of the disaster that occurred, the Government of Indonesia failed to protect the community from the risk of such a disaster. Furthermore, based on the Disaster Risk Reduction criteria, the rehabilitation and reconstruction that have been carried out are relatively adequate. However, non-structural aspects of mitigation, which is one of the important aspects of disaster risk reduction, have not been carried out. Disaster training and simulations so far have only been done once and not regularly, therefore jeopardizing the community's preparedness for future occurrences of natural disasters. Therefore, improvements in disaster management need to be done in Indonesia